CHARACTERISTICS OF CORN YOGHURT WITH ADDITION OF SKIM AND KARAGENAN MILK - Ria Dewi Andriani, Premy Puspitawati . (Jurnal Sains Peternakan, 2016)
ABSTRACT This study aims to determine the characteristics of corn yoghurt with the addition of carrageenan and skim milk. The study was conducted using Completely Randomized Design with two factors and three replications. The treatment used in this research is the concentration of skim milk and carrageenan. The results showed that the addition of skim milk and carrageenan in corn yoghurt showed significant different effect (P 0.05) on the fat content. From the results of the study average protein, fat content, total acid, pH, and viscosity were 4.11-4.46%; 0.88-0.91%; 0.93-0.98%; 4,73-4,49; and 390,89-416,00 cp. Keywords: yoghurt, corn extract, skim milk, carrageenan